tert-Butyl 2-[4-(2-{4-[(tert-butoxycarbonyl)methoxy]-3-methylphenyl}-2-propyl )-2-methylphenoxy]acetate - Ali, Q.; Yousuf, S.; Shah, M.R.; Ng, S.W. (International Union of Crystallography, 2010)
In the molecule of the title compound, C(29)H(40)O(6), the carbon atom belonging to the propyl chain is connected to two aromatic rings that open up the C(aryl)-C-C(aryl) angle to 111.5 (1)degrees. The four-atom -O-CH(2)-C(=O)-O- linkage between the aromatic ring and the tert-butyl group assumes a (-)anti-periplanar conformation for one substituent and a (-)syn-periplanar conformation for the other substituent; the O-C-C-O torsion angles are -173.7 (2) and -10.2 (3)degrees.